2007
DOI: 10.1002/yea.1508
|View full text |Cite
|
Sign up to set email alerts
|

On‐line measurements of oscillating mitochondrial membrane potential in glucose‐fermenting Saccharomyces cerevisiae

Abstract: We employed the fluorescent cyanine dye DiOC 2 (3) to measure membrane potential in semi-anaerobic yeast cells under conditions where glycolysis was oscillating. Oscillations in glycolysis were studied by means of the naturally abundant nicotinamide adenine dinucleotide (NADH). We found that the mitochondrial membrane potential was oscillating, and that these oscillations displayed the same frequency and duration as the NADH oscillations. It was confirmed that DiOC 2 (3) localizes itself in the mitochondrial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…As for the F 0 F 1 ATPase the activity needs to be tightly controlled for oscillations to occur. Both inhibition of the ATPase by azide or stimulation of the ATPase by FCCP will result in the disappearance of the oscillations (16,21). Presumably the same applies to PMA1, although it has not yet been documented that an increase in the activity of this enzyme will make the oscillations disappear.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As for the F 0 F 1 ATPase the activity needs to be tightly controlled for oscillations to occur. Both inhibition of the ATPase by azide or stimulation of the ATPase by FCCP will result in the disappearance of the oscillations (16,21). Presumably the same applies to PMA1, although it has not yet been documented that an increase in the activity of this enzyme will make the oscillations disappear.…”
Section: Discussionmentioning
confidence: 95%
“…Previous experiments suggested that the two main ATP consuming processes are ATP hydrolysis by the mitochondrial F 0 F 1 ATPase and the plasma membrane ATPase (PMA1) (16). ATP hydrolysis by the F 0 F 1 ATPase is associated with pumping of protons out of the mitochondria which again results in the generation of a mitochondrial membrane potential (16,21) and because the intracellular ATP concentration is oscillating the mitochondrial membrane potential is oscillating too as shown in Fig. 3D.…”
Section: A New Atp Nanobiosensor To Measure Intracellular Atp-mentioning
confidence: 90%
See 2 more Smart Citations
“…These include levels of nicotinamide adenine dinucleotide (NAD) which can be seen to oscillate between the oxidized (NAD + ) and reduced forms (NADH), as well as other glycolytic intermediates, including glucose-6-phosphate, fructose-6-phosphate and fructose 1,6-bisphosphate [1]. Glycolytic oscillations are accompanied by oscillations in mitochondrial membrane potential (Δψ m ) [2]. This phenomenon has been observed for over 40 years [3] and is known as glycolytic oscillations [4].…”
Section: Introductionmentioning
confidence: 99%